1984
DOI: 10.1007/bf00687613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on glial fibrillary acidic protein in peritumorous edema of cats: A morphometric study

Abstract: In 54 cats experimental brain tumors were produced by xenotransplantation of the blastomatous glial cell clone RG2 into the internal capsule of the left hemisphere. Fifteen of these animals were treated with dexamethasone for 1 week and four animals for 2 h. The occurrence of glial fibrillary acidic (GFA) protein in tumor and peritumoral edema was studied by immunocytochemistry at intervals ranging between 3 and 35 days after implantation. High concentrations of GFA protein were present in giant and many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The histologic effects of tumor on the surrounding brain tissue were evaluated by the quantitative analysis of the local astrocytic reaction. Astrocytes respond to various kinds of brain lesion by hypertrophy and proliferation as well as an increase in GFAP content [4,16,17]. This reaction is supposedly induced by the extravasated serum components [16,18,19] or other materials in the edema fluid released from the damaged tissue [20,21].…”
Section: In(~) [ ] ( + ) L--l-(-)mentioning
confidence: 99%
“…The histologic effects of tumor on the surrounding brain tissue were evaluated by the quantitative analysis of the local astrocytic reaction. Astrocytes respond to various kinds of brain lesion by hypertrophy and proliferation as well as an increase in GFAP content [4,16,17]. This reaction is supposedly induced by the extravasated serum components [16,18,19] or other materials in the edema fluid released from the damaged tissue [20,21].…”
Section: In(~) [ ] ( + ) L--l-(-)mentioning
confidence: 99%
“…This decrease was accompanied by a decrease in the number of HRP-containing small endothelial vesicles. These data suggest that dexamethasone influences cerebral edema by decreasing the permeability of the cerebral vasculature for macromolecules.Hedley-Whyte ET, Hsu DW: Effect of dexamethasone on blood-brain barrier in the normal mouse.Ann Neurol 19373-377, 1986 Dexamethasone reduces increased intracranial pressure resulting from cerebral edema associated with brain tumors and pseudotumor [7, 12, 16,23,26,29,34,39, 451 [24] are each associated with a decrease in the permeability of the blood-brain barrier for macromolecules suggests that dexamethasone might also affect the normal blood-brain barrier. Since the mouse brain normally has a number of horseradish peroxidase-permeable arteries (or arterioles) [ l 5 , 17, 46, 471, and its normal brain water content is decreased by hydrocortisone treatment 14 11, the normal mouse seemed to be a suitable model to study the effect of dexamethasone on the normal blood-brain barrier.…”
mentioning
confidence: 99%
“…Considering that the CNS is an immunoprivileged organ due to the blood‐brain barrier and that only a few infiltrating lymphocytes were detected in our specimens, the finding that intracranial tumours were sensitive to systemic mAb treatment raises the question of whether or not other specialized resident immune cells, such as microglia, or alternative members of the brain microenvironment increase distinct anti‐tumoural immune response. In addition, it has to be considered that a preoperative steroid treatment that avoids peritumoural oedema and is often applied in glioblastoma patients, might lead to a decreased glial reactivity and a diminished lymphocytic invasion [24–27]. In vitro studies revealed that TNFRSF9 is up‐regulated by astrocytes upon stimulation with the Ca(2+)‐binding protein S100B that is frequently increased during CNS pathologies [28].…”
Section: Discussionmentioning
confidence: 99%